The Disaster Preparedness Educationthrough Triangle Alert Game To Increase Children's Independence In Tunas Bangsa Kindergarten In Dealing With Disasters In Coastal Area - Yanti, Desy Dwi; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2019)
Disasters cannot be avoided but can be muted if the community has sufficient information about disaster prevention. The lack of information had about what should be done when a disaster occurs, especially for children, makes them vulnerable to disasters. Therefore, education about disaster preparedness is very necessary for early childhood. The purpose of this study is to determine whether there is an influence on the implementation of disaster education through a triangle alert game on children's independence when facing disasters in the coastal area of Bonang District, Demak Regency. Through the triangle alert game, it can be seen whether there are differences in the level of independence of children when facing a disaster. The research method in this research is an experiment. The study uses the one-group pretest-posttest design method.An experiment is carried out in one group without a comparison group. The research instrument with the parameters of independence uses a Likert scale with answers "Strongly Agree", "Agree", "Disagree", and "Disagree". The population in this study is the children in Tunas Bangsa Kindergarten of Morodemak Village Bonang District Demak Regency. The sample in this study is 33 children of Kindergarten B in Tunas Bangsa Kindergarten. The data analysis techniques in this study are descriptive analysis, normality test, and hypothesis testing with Paired Sample t-Test. The hypothesis test states that Ho is rejected and Ha is accepted. The results of the t-test calculation between the pretest and posttest of the experimental group are tcount = -12,419 with value of sig (2-tailed) < 0.05. The average value at the pretest stage is 68.00 and at the posttest stage is 93.55. So, there is a significant difference between children's independence in facing disasters before and after being given disaster preparedness education.